The case for weak null in English - Tollet, Andrew (Kalbotyra, 2023)
The concept of the null article in English was originally developed as a means of explaining the apparent paradox that singular nouns with the same surface form, namely the non-presence of a grammatical article, are used in quite different communicative situations. Null has been described as the most definite form in the English article system, standing in direct contrast to zero at the opposite end of a scale. Yet, while this may applicable in the case of predicates nouns denoting unique roles, certain institutions where the referent is pragmatically unique, or coordinate structures with a preceding referent, there is persuasive evidence to suggest a considerable number of other null structures do not fit such a description but, on the contrary, share common characteristics with the weak form of the definite article or occupy more of a neutral position which would permit insertion of either one of the surface articles. On this basis, a proposal is advanced to acknowledge two forms of the null article, strong and weak, according to context. Rather than a corpus-based statistical approach, this paper draws upon a smaller selection of contemporary, non-fictional texts from a variety of semantic fields to illustrate the points being made.